O agir argumentativo no gênero Multimodal Vlog - Sousa, Fabiano Mesquita de (2024)
This dissertation was carried out based on research developed at Professional Master's Program in Modern Languages/ Linguistics at the Federal University of Ceará with the purpose of investigate the understanding of the multimodal vlog genre regarding the manifestation of argumentation and multiliteracies in the light of ISD and Visual Design Grammar. It started from the premise that the school must incorporate new ways for students to interact in the most different communication situations produced in the digital environment and turn its attention to the teaching of oral genres in terms of textual understanding, without just excelling, as did the society throughout its history, by certain language practices such as written/printed culture, disregarding others such as digital. This initial finding motivated the selection of vlogs belonging to the journalistic-media field and posted on channels that address environmental activism on YouTube, in which language is used that is closer to the reality of students in the 9th year of elementary school and socially relevant content. and current approaches to promoting critical literacy and multiculturalism in Portuguese teaching. To discuss the object, it was based on theoretical contributions from authors such as Bronckart (2023), Rojo (2012), Volóchinov (2013), among others, and on official documents such as the National Common Curricular Base (2018). Methodologically, the present work adopts a qualitative approach and assumes a bibliographic, documentary and propositional character, using the didactic itinerary as a device for the oral understanding of this genre in Portuguese language classes in the face of new forms of reading, a new way of positioning oneself and to construct arguments. This device, which allows students to develop their language skills when learning a multimodal genre, also considers verbal transcriptions of the aforementioned vlogs and visual resources, as well as text organization layer categories, for the analysis of the production context, thematic content, textualization mechanisms and enunciative and non-linguistic means. The contributions, triggered by this research, will serve the student as an opportunity for critical literacy in the interpretation and reflection on topics covered in the vlogs and the teacher as inspiration for the creation and experimentation of teaching materials focused on reading/listening to texts oral, multisemiotic and multimedia, improving teaching practice and, in effect, the field of teaching.